The development of uncertainty monitoring during kindergarten: Change and longitudinal relations with executive function and vocabulary in children from low‐income backgrounds. Issue 2 (10th December 2021) - Gonzales, Christopher R.; Merculief, Alexis; McClelland, Megan M.; Ghetti, Simona
Abstract: Children's ability to monitor subjective feelings of uncertainty (i.e., engage in uncertainty monitoring) is a central metacognitive skill. In the current study, we examined the development of uncertainty monitoring as well as its relations with vocabulary and executive function development in children ( N  = 137, 52% female) from predominately White and Latinx/Hispanic backgrounds when they were 4–6 years old and enrolled in a Head Start preschool and kindergarten between 2018 and 2019. We found that children's uncertainty monitoring improved during the kindergarten year. Children's executive function and vocabulary in preschool and vocabulary growth from preschool to kindergarten predicted uncertainty monitoring at the end of kindergarten, which sheds new light on potential mechanisms supporting children's metacognitive development.